Exploring the Polyadenylated RNA Virome of Sweet Potato through High-Throughput Sequencing - Gu, Ying-Hong (Public Library of Science, 2014)
BACKGROUND: Viral diseases are the second most significant biotic stress for sweet potato, with yield losses reaching 20% to 40%. Over 30 viruses have been reported to infect sweet potato around the world, and 11 of these have been detected in China. Most of these viruses were detected by traditional detection approaches that show disadvantages in detection throughput. Next-generation sequencing technology provides a novel, high sensitive method for virus detection and diagnosis. METHODOLOGY/PRINCIPAL FINDINGS: We report the polyadenylated RNA virome of three sweet potato cultivars using a high throughput RNA sequencing approach. Transcripts of 15 different viruses were detected, 11 of which were detected in cultivar Xushu18, whilst 11 and 4 viruses were detected in Guangshu 87 and Jingshu 6, respectively. Four were detected in sweet potato for the first time, and 4 were found for the first time in China. The most prevalent virus was SPFMV, which constituted 88% of the total viral sequence reads. Virus transcripts with extremely low expression levels were also detected, such as transcripts of SPLCV, CMV and CymMV. Digital gene expression (DGE) and reverse transcription polymerase chain reaction (RT-PCR) analyses showed that the highest viral transcript expression levels were found in fibrous and tuberous roots, which suggest that these tissues should be optimum samples for virus detection. CONCLUSIONS/SIGNIFICANCE: A total of 15 viruses were presumed to present in three sweet potato cultivars growing in China. This is the first insight into the sweet potato polyadenylated RNA virome. These results can serve as a basis for further work to investigate whether some of the 'new' viruses infecting sweet potato are pathogenic.